Is body weight dissatisfaction a predictor of depression independent of body mass index, sex and age? Results of a cross-sectional study - Aline Richard; Sabine Rohrmann; Tina Lohse; Monika Eichholzer (BMC, 2016)
Abstract Background Little is known about the association of dissatisfaction with body weight - a component of body image - with depression in individuals of different sex, age, and with different body mass index (BMI). Hence, the aim of our study was to evaluate the association of body weight dissatisfaction (BWD) with depression in different sub-groups. Methods We analyzed data of 15,975 individuals from the cross-sectional 2012 Swiss Health Survey. Participants were asked about their body weight satisfaction. The validated Patient Health Questionnaire (PHQ-9) was used to ascertain depression. Age was stratified into three groups (18-29, 30-59, and ≥60 years). The body mass index (BMI) was calculated from self-reported body height and weight and categorized into underweight (BMI <18.5 kg/m2), normal weight (BMI 18.5-24.9 kg/m2), overweight (BMI 25.0-29.9 kg/m2), and obesity (BMI ≥30 kg/m2). The association between body weight dissatisfaction (BWD) and depression was assessed with logistic regression analyses and odds ratios (OR) with 95 % confidence intervals (CI) were computed. Results BWD was associated with depression in the overall group (OR 2.04, 95 % CI 1.66-2.50) as well as in men (OR 1.85, 95 % CI 1.34-2.56) and women (OR 2.25, 95 % CI 1.71-2.96) independent of BMI. The stratification by age groups showed significant associations of BWD with depression in young (OR 1.78, 95 % CI 1.16-2.74), middle-aged (OR 2.10, 95 % CI 1.61-2.74) and old individuals (OR 2.34, 95 % CI 1.30-4.23) independent of BMI. Stratification by BMI categories resulted in statistically significant positive associations of BWD and depression in underweight, normal weight, overweight and obese individuals. Conclusion BWD was associated with depression independent of BMI, sex and age.